Street-Level Workers and Unaccompanied Minors: Between Vulnerability and Suspicion - Clerc, Sélim (My University, 2022)
Abstract: Focusing on practices and representations mobilized by street-level workers in the management of North African unaccompanied minor migrants (UAMs) in Geneva, I take a closer look at the everyday assessment and production of UAMs’ deservingness in the context of humanitarianism. I show the importance of doubt and of perceived vulnerability in the informal evaluation process of UAMs’ right for protection. I further demonstrate how the social construction of childhood, race, and gender influence street-level workers’ perceptions. Résumé : Dans cet article j’étudie les pratiques et les représentations mobilisées par les « street-le- vel workers » dans la gestion des migrant·es mineur·es non-accompagné·es (MNA) maghrébin·es à Genève. Dans le contexte de l’humanitarisme, j’explore la production quotidienne de la légitimité des MNA. Je montre l’importance du doute et de la vulnérabilité dans le processus informel d’évaluation du droit à la protection des MNA, et je révèle l’impact de la construc- tion sociale de l’enfance, de la race et du genre sur les perceptions de ces professionel∙les. Zusammenfassung: Der vorliegende Artikel untersucht die Praktiken und Repräsentationen die von “street-level workers” bei der Betreuung von unbegleiteten maghrebinischen Minder- jährigen (MNAs) in Genf mobilisiert werden. Ich werfe einen Blick auf die humanitaristische Herstellung der Legitimität von MNAs und erörtere die Bedeutung von Verdächtigung und Verwundbarkeit im informellen Beurteilungsprozess des Rechts auf Schutz. Ausserdem zeige ich, wie die soziale Konstruktion von Kindheit, Ethnizität und Geschlecht die Wahrnehmun- gen der Berufstätigen beeinflusst.
Keywords: Migration; street-level workers; humanitarianism; race; gender